Same Process, Different Outcomes: Group Performance in an Acquiring a Company Experiment - Marco Casari; Jingjing Zhang; Christine Jackson (Institute for the Study of Labor (IZA), 2015)
It is still an open question when groups perform better than individuals in intellective tasks. We report that in an Acquiring a Company game, what prevailed when there was disagreement among group members was the median proposal and not the best proposal. This aggregation rule explains why groups underperformed with respect to a "truth wins" benchmark and why they performed better than individuals deciding in isolation in a simple version of the task but worse in the more difficult version. Implications are drawn on when to employ groups rather than individuals in decision making.
Keywords: C91; C92; D03; D81; 330; winner's curse; group decision making; communication; risky shift; herd behavior